Synthesis and characterization of calcium-based catalysts for transesterification of Jatropha curcus L. and Nannochloropsis oculata oils to biodiesel - Teo, Siow Hwa (2015)
Catalyst plays an important role in biodiesel production. The current transesterification technology using homogeneous liquid catalysts in biodiesel production process is uneconomical, largely due to liquid catalyst is corrosive, difficult to be separated and regenerated in order to reuse. Additional, the high price of biodiesel is largely due to feedstock prices. Therefore, biodiesel price can be reduced by utilizing non-edible oil feedstock and heterogeneous solid catalysis on transesterification reaction for biodiesel production. The use of heterogeneous catalysis on the other hand, prevents the undesirable saponification, allows process simplification and offers reduction in the processing cost. In this study, fatty acid methyl ester (FAME) was synthesized by transesterification of Jatropha curcas L. crude oil with methanol using calcium based heterogeneous catalysts. The initial part of this project was to synthesize the catalysts and followed by characterized the prepared catalysts i.e. calcium lanthanum (CaO-La2O3), calcium cerium (CaO-CeO2), calcium nickel (CaO-NiO2), calcium neodymium (CaO-Nd2O3) and calcium methoxide (Ca(OCH3)2). The optimization of the transesterification of J. curcas crude oil using different heterogeneous calcium based catalysts was evaluated. The relative order of effectiveness on transesterification was Ca(OCH3)2 > CaO-CeO2 > CaO-La2O3 > CaO-NiO2 > CaO-Nd2O3. The TPD results demonstrated that mixed metal oxides that prepared by co-precipitation method, showed an extremely high FAME yield (85~95%) due to the presence of stronger basic strength on the catalytic site of catalysts. Moreover, all catalysts can be regenerate and reuse. The produced FAME is met ASTM D6751 and European 14214 international biodiesel standards.In the second part of investigation, cultivation, extraction and methanolysis of crude microalga’s (Nannochoropsis oculata) oil were carried out. Catalytic screening was performed on Ca(OCH3)2 and mixed oxide catalysts, where Ca(OCH3)2 catalyst revealed to be the superior performance in fast conversion of microalgae derived crude oil to FAME using transesterification technique. Ca(OCH3)2 was prepared via hydrothermal route, resulted in a catalyst with surface area, total pore volume and average pore diameter of 30.5 m2 g-1, 0.21 cm3 g-1 and 31.97 nm, respectively. Photoautotrophic cultivated N. oculata, then followed by treansesterificaition of extracted crude oil with methanol in the presence of Ca(OCH3)2 catalyst, gave a FAME yield of 95.78 %. It was observed that methanol volume and catalyst concentration were the important factors attributed to high yield of biodiesel from crude microalgae oil. The experiment results showed that catalytic transesterification technique has the potential to provide energy-efficient routes for biodiesel production form algae biomass.